European Structural Funds During the Crisis: Evidence from Southern Italy - Guido De Blasio; Emanuele Ciani (European Regional Science Association (ERSA), 2015)
We investigate the effectiveness of European Structural Funds on employment, population and house prices in Local Labor Markets (LLM) located in Southern Italy. We exploit the variability in disbursements between 2007 and 2013 and estimate the impact of the interventions by allowing for LLM-specific fixed features and LLM-specific time trends. We find that the ability of these funds to offset the negative consequences of the economic crisis seems to have been limited.
Keywords: J01; J23; J61; 330; place-based policies; eu structural funds; local labor markets